A determination of time spent on nursing activities in a labour ward in a midwife obstetrics unit - Ngidi, Duduzile Florence (My University, 2017)
Determination of staffing needs is a priority for an organization seeking to provide safe patient care in an environment which is cost conscious. Registered nurses and midwives spend more time with patients than any other single category of health professionals and also provide 24 hour direct patient care. Activity based norms are recognized by the World Health Organization to be the most suitable way of determining staffing needs; establishing of time spent on activities is one of the key factors in determining activity based staffing norms. This study focuses on ascertaining the timing of activities of midwives during labour in maternity obstetrics units with the possibility of using the information at a later date to determine activity based staffing norms for midwives in the maternity obstetrics units. An adaptation of Hodnett’s (1996) five categories of labour support was used as a framework for measuring activities performed by midwives and nurses while supporting women in labour. This model was adapted from the previous work sampling study conducted in Toronto (McNiven and Hodnett, 1992:1). Purpose of the study The purpose of the study was to determine the time taken to perform nursing activities during labour in South African Midwife Obstetrics Units (MOUs) to inform the future process of developing nursing norms for labour wards in MOUs in the public sector. Research design This was an exploratory observational study using a mixed method design that included both qualitative and quantitative methods. Spot observations studies were conducted during patients’ first stage of labour, which constituted the quantitative part of the design, i.e. activities observed and measured during the observation period. Naive sketches were used in the qualitative part of the study. The study was conducted in the six Midwife Obstetrics Units in Ekurhuleni Metropolitan Health District of Gauteng. v Main findings Activities carried out by midwives in the MOUs were mainly reactive to the physiological processes of labour as they occur. Midwives in MOUs did not display the “soft skills” referred to in Hodnett’s categories of labour support. On the other hand, those skills that they managed to display were not easy to capture because they happen simultaneously with other activities e.g. touching and holding. Most of the categories of labour support were difficult to measure because they occurred very quickly and in “groups/batches.” The activities of midwives when caring for patients in labour were timed, and the calculation of the frequency at which nursing activities was carried out was particularly successful, but the researcher concluded that while the study was useful to provide insights into the quality of care, these results could not be used as a basis for determining activity based norms. This is due to the fact that the midwives did not practice quality care and the observation method was difficult to implement. The tool would need to be simplified and the possible use of technology such as videos should be considered if the study were to be replicated. Factors that influenced the time spent and the duration of activities relate to communication, relationships, resources and systems failures. Conclusion The categories of labour support can be used for improving patient care and, if adapted to the South African setting, could be fit for the purpose of developing activity based norms, but only once midwives are taught and encouraged to implement the “soft skills” in labour which are necessary but seldom practiced. Key concepts: Maternity obstetrics unit, workload, activity based norms, categories of labour support.
Keywords: Labor, Obstetric; Nursing Services; Midwifery